La ferme comme laboratoire ou l’architecture expérimentale de Charles Gilbert de Morel-Vindé (1759-1842) - Valérie Nègre (In Situ)
Charles Gilbert de Morel-Vindé shares many of the characteristics of his contemporaries. Convinced that agriculture is the founding principle of all political economy and that the farmer is “an industrialist who forces living nature to produce abundantly at the lowest possible cost”, he is one of a large number of land-owning agronomists who apply positive science to the art of agriculture. He is an interesting character in that the extent of his wealth and his eminent social position allow him to transform his properties “into experimental and exemplary farms” and to establish new models for rural buildings. His publications deserve our attention as they allow us to observe the development of models whose form and placement are determined by a logic which is independent of any relationship with their surroundings, in other words, buildings which do not take characteristics related to environment, culture and identity into account. It is the emergence of this phenomenon which would be classified nowadays as “de-territorialisation” that we propose to examine in this article in the light of some of the agronomist’s projects.